Designing EVE (English Vocabulary Exercises) by using Hot Potatoes as supplementary material for teaching vocabulary to elementary level students - Ahmad Lukmanul Hakim (Language and Education Journal, 2021)
This research was conducted in order to create EVE, an electronic game that can be used to teach and learn vocabularies. The objectives of this research is to see whether EVE can be used to teach vocabulary to elementary school students as a supplementary teaching media. This research takes the form of developmental research. This developmental research was performed in order to create new teaching materials. The research method consists of four phases: analyzing, designing, developing, and implementing also known as ADDI method. Several vocabulary materials from different books and sources were combined with the Hot Potatoes application for teaching vocabularies to complete the designed product. The EVE was created for approximately 50 minutes in teaching and learning period. The completed research was implemented with 11 elementary students from different schools. To sum it up, the researcher found that EVE is usable for teaching vocabulary to elementary level students especially in gaining students’ interest and motivate students to learn vocabulary in more pleasing way.